The Medical Manipulation of Reproduction to Implement the Nazi Genocide of Jews - Chalmers, Beverley (Conatus - Journal of Philosophy, 2019)
Holocaust literature gives exhaustive attention to direct means of exterminating Jews, by using gas chambers, torture, starvation, disease, and intolerable conditions in ghettos and camps, and by the Einsatzgruppen. In some circles, the term “Holocaust” has become the ultimate description of horror or horrific events. The Nazi medical experiments and practices are an example of these. Nazi medical science played a central and crucial role in creating and implementing practices designed to achieve a “Master Race.” Doctors interfered with the most intimate and previously sacrosanct aspects of life in these medical experiments – reproductive function and behavior – in addition to implementing eugenic sterilizations, euthanasia, and extermination programs. Manipulating reproductive life – as a less direct method of achieving the genocide of Jews – has been less acknowledged. The Nazis prevented those regarded as not meeting idealized Nazi racial standards – and particularly Jewish women – from having sex or bearing children through legal, social, psychological and biological means, as well as by murder. In contrast, they promoted reproductive life to achieve the antithesis of genocide – the mass promotion of life – among those deemed sufficiently “Aryan.” Implementing measures to prevent birth is a core feature of the UN Convention on the Prevention and Punishment of Genocide. As with many other aspects of the Holocaust, science and scientists were inveigled into providing legitimacy for Nazi actions. The medical profession was no exception and was integrally involved in the manipulation of birth to implement the Holocaust.